Role of Fine Needle Aspiration Cytology in Evaluation of Cervical Lymphadenopathy - Harsimrat Singh; Abhay Kumar Singh; Inderpreet Singh Oberoi (Indian Journal of Forensic Medicine & Toxicology, 2022)
Introduction: Cervical lymphadenopathy is one of the commonest clinical presentations of patients ofhead and neck pathologies. Metastatic cervical lymphadenopathy is a common presentation in head andneck oncology. The aim of this study is to evaluate the effectiveness of FNAC as a primary investigationtool.Aims and Objectives: The aim of the study was to evaluate the effectiveness of FNAC in diagnosingcervical lymphadenopathy.Material and Methods: A study was conducted in the Department of Pathology and E.N.T.,SIMS, Hapur, U.P., India from January 2019 to February 2020 which included 52 patients withcervical lymphadenopathy presenting to outpatient clinics. FNAC was done in patients of cervicallymphadenopathy before surgery or incision/excision biopsy and the results of FNAC was correlatedwith histopathological evaluation.Results: In our study 88.47.% of sensitivity and specificity of 92.03% was found on FNAC of cervicallymph nodes.Conclusion: FNAC remains a safe, cost effective and appropriate first line investigation though theresults have to be confirmed with HPE for proper evaluation and management.